2016
DOI: 10.1155/2016/4878246
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Medical Adhesive Tapes in Patients at Risk of Facial Skin Trauma under Anesthesia

Abstract: Introduction. Adhesive tapes are used for taping eyelids closed and securing endotracheal tubes during general anesthesia. These tapes can cause facial skin injury. We compared the incidence of facial skin injury and patient satisfaction with different tapes used. Methods. A total of 60 adult patients at risk of skin trauma were randomized to use 3M™ Kind Removal Silicone Tape or standard acrylate tapes: 3M Durapore (endotracheal tube) and Medipore (eyelids). Patients were blinded to tape used. Postoperatively… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(36 citation statements)
references
References 30 publications
0
30
0
6
Order By: Relevance
“…■ Close the eyes and prevent corneal abrasions. 44 Skin on the face, particularly the eyelids, is thin and delicate, making it susceptible to medical adhesive-related skin injury. The Association for Perioperative Practice (AfPP) therefore recommends that the use of tape, other than to secure eye pads, should be avoided 45 ■ Fix devices such as endotracheal tubes, temperature probes, gastric tubes and electrodes Surgical adhesive tapes often contain acrylate, the adhesiveness of which increases over time.…”
Section: Top Tipsmentioning
confidence: 99%
“…■ Close the eyes and prevent corneal abrasions. 44 Skin on the face, particularly the eyelids, is thin and delicate, making it susceptible to medical adhesive-related skin injury. The Association for Perioperative Practice (AfPP) therefore recommends that the use of tape, other than to secure eye pads, should be avoided 45 ■ Fix devices such as endotracheal tubes, temperature probes, gastric tubes and electrodes Surgical adhesive tapes often contain acrylate, the adhesiveness of which increases over time.…”
Section: Top Tipsmentioning
confidence: 99%
“…When evaluating the adhesives used in the intraoperative period, another study concluded that the silicone adhesive caused less facial skin lesions when compared to the standard acrylate adhesive, generating greater comfort to the patient. These findings highlight the importance of knowing the properties of the materials to select the most suitable products for care, aiming to promote patient safety and comfort (Zeng, Lie, & Chong, ).…”
Section: Discussionmentioning
confidence: 98%
“…They found that the use of silicone adhesive material resulted with a greater patient satisfaction and lesser skin injury. Thus, silicone rather than acrylate seems to be a safer option for the occlusion of eyelids during anesthesia [6].…”
Section: Discussionmentioning
confidence: 99%